Development of Dashboard Features on the Information System of the Institute for Research and Community Service to Support the Reporting of Community Service Data - Wibawa, Rindu Puspita; Prismana, I Gusti Lanang Putra Eka (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Community service is one of the core obligations of higher education institutions aimed at applying science and technology to address societal problems. State University of Surabaya, through the Institute for Research and Community Service, has implemented an information system to manage community service activities conducted by its lecturers. However, the existing system does not yet provide detailed and comprehensive information to support effective monitoring and reporting processes. This study aims to develop a dashboard feature that presents detailed and structured community service data to improve reporting quality and support decision-making for university leaders and stakeholders. The development process followed the Waterfall method, consisting of requirement definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The resulting dashboard provides various visualizations, including the percentage of community service activities, participant distribution, inter-faculty involvement, and detailed activity information. The implementation results show that the developed dashboard feature enhances the accessibility and clarity of community service data, supports monitoring and evaluation processes, and improves the effectiveness of reporting community service activities at the State University of Surabaya. This dashboard offers practical value by enabling role-based, integrated, and transparent monitoring of community service activities within a single institutional system.